Radiation Beam Width and Beam Direction Electronic Control of Transparent and Compact Vivaldi Antennas - Amani Cherif; Mohamed Himdi; Xavier Castel; Quentin Simon; Saber Dakhli; Fethi Choubani (Applied Sciences, 2023)
In this paper, we present a study on a broadband transparent tapered slot antenna. In general, the objective of achieving optical transparency is to enable antennas to seamlessly integrate into windows, offering an aesthetically pleasing and inconspicuous appearance. The aim of our research is to develop antennas that possess the ability to adjust horizontal plane beams across a wide frequency range, from 24 to 28 GHz, for 5G applications. This structure combines three antennas into a single unit, providing an advantage in terms of saving space. Furthermore, this structure offers the possibility of choosing between using a single antenna to obtain a directional beam in the −90°, 0°, or +90° directions (depending on the activated antenna) corresponding to three states, or the combination between two states to obtain another three additional states. The combination of the three states also allows for the acquisition of another state. At this point, the total number of states is 23 − 1. Only three PIN diodes are employed to switch between all states. Additionally, by adjusting the bias values of the PIN diodes, which function as variable resistors, the antenna beamwidth can be adjusted in order to achieve a coverage of 300°, offering more radiation pattern reconfigurability. The proposed method offers several advantages, including simplicity and feasibility in controlling the beamwidth and the beam direction electronically. This structure can be easily integrated into the development of fifth-generation communication systems.